I've got algorithm (Money Marketing, 2012)
Having just returned from the US, visiting a number of the 'next generation' advice propositions, I believe more than ever that organisations of this the type will fundam-entally transform the advice process in this country over the next five years or so. JP Morgan's recent research on consumer attitudes to paying for advice suggests 800,000 UK households might pay for ongoing advice but a further 2.4 million families would consider paying for a case-by-case-type service. Ofcom also identified fundamental changes in the way in which consumers are sourcing information. One of the major new trends is 'Turfing', when people surf the internet using perhaps a laptop but predominantly a tablet or smartphone at the same time as watching the TV. Tablet ownership in the UK has increased from 2 per cent to 11 per cent of the population in just 12 months and if you look at the demographics of ownership, not surprisingly, it is the wealthier consumers who are the biggest group of adopters - in AB socio-economic groups it nearly doubles to 19 per cent.